Analisis Gaya Kepemimpinan Kepala Desa Tosora Kecamatan Majauleng Kabupaten Wajo - Putri Handayani; Eka Patmasari; Yuniarni Yuniarni (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
This research aims to analyze the leadership style of the Head of Tosora Village, Majauleng District, Wajo Regency. Leadership at the village level has a significant influence on the performance of village officials and the quality of services to the community. Using a qualitative approach with a case study method, this research collected data through interviews with village officials and the community. The research results show that the leadership style applied includes a clear vision, responsiveness to community needs, and the ability to motivate and develop team capacity. These findings underline the importance of character and effective leadership methods in achieving organizational goals, as well as the vital role of village heads in carrying out government functions efficiently.